2014
DOI: 10.1155/2014/767061
|View full text |Cite
|
Sign up to set email alerts
|

Potent Anti-Inflammatory Activity of Pyrenocine A Isolated from the Marine-Derived FungusPenicillium paxilliMa(G)K

Abstract: Very little is known about the immunomodulatory potential of secondary metabolites isolated from marine microorganisms. In the present study, we characterized pyrenocine A, which is produced by the marine-derived fungus Penicillium paxilli Ma(G)K and possesses anti-inflammatory activity. Pyrenocine A was able to suppress, both pretreatment and posttreatment, the LPS-induced activation of macrophages via the inhibition of nitrite production and the synthesis of inflammatory cytokines and PGE2. Pyrenocine A also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 39 publications
0
11
1
Order By: Relevance
“…showed immunosuppressive and anti‐inflammatory activity . Marine fungus has also been a source for few anti‐inflammatory compounds such as mangicols A and B (sesterterpenes), mycoepoxidiene, penstyrylpyrone, and pyrenocine A . However, the present study revealed the anti‐inflammatory efficacy of the potential strain VITGAP173 isolated from Pichavaram regions.…”
Section: Resultscontrasting
confidence: 52%
“…showed immunosuppressive and anti‐inflammatory activity . Marine fungus has also been a source for few anti‐inflammatory compounds such as mangicols A and B (sesterterpenes), mycoepoxidiene, penstyrylpyrone, and pyrenocine A . However, the present study revealed the anti‐inflammatory efficacy of the potential strain VITGAP173 isolated from Pichavaram regions.…”
Section: Resultscontrasting
confidence: 52%
“…It is worth mentioning that inflammatory cytokines have stimulated [ 62 , 63 , 64 , 65 ] cells to synthesize other inflammatory cytokines, namely, IL-1β, TNF-α, IL-6, IL-8, and chemokines. The anti-inflammatory cytokines are a series of immune-regulatory molecules [ 34 , 50 , 66 , 67 ] that control the pro-inflammatory cytokine response.…”
Section: Resultsmentioning
confidence: 99%
“…Compound (28) was identified as 6,7-dihydroxy-2,2-dimethyl-4-chromanone, first synthesized in 1937. 38 Related compounds displayed antioxidant activity and are used as inhibitors of self-oxidation of various organic substrates such as plastics, lubricants and rubber products often exposed to air during manufacturing processes. 38,39 Production of (28) by Cochliobolus spp.…”
Section: Resultsmentioning
confidence: 99%